S Velocity Model of East Asia From a Cluster Analysis of Localized Dispersion. Issue 11 (8th November 2018) - Witek, M.; van der Lee, S.; Kang, T.‐S.; Chang, S.‐J.; Ning, J.; Ning, S.
Abstract: We measured Rayleigh wave group velocity dispersion curves from station pair cross correlations of continuous broadband data from 1, 082 seismic stations in regional networks across China, Korea, and Japan. The dispersion curves are localized in the period range 6–40 s to produce group velocity maps, which we then combine with group velocity data in the period range 50–133 s from the global dispersion model of Ma et al. (2014, https://doi.org/10.1093/gji/ggu246 ). Cluster analysis performed on the local dispersion curves reveals distinct tectonic regions and provides a new way of estimating the number of regions needed to describe a surface wave dispersion data set. We inverted the centroid dispersion curves corresponding to each cluster for a new set of reference models. We used a combination of teleseismic receiver functions and Moho depths from the LITHO1.0 model to create a 3‐D Moho depth reference model and then constructed a 3‐D S velocity model by jointly inverting group velocities with localized phase velocities in the period range 28.57–200 s, also from Ma et al. (2014, https://doi.org/10.1093/gji/ggu246 ). The cluster analysis and comparisons with other regional models provide evidence for a broad region of deformed lithosphere in East Asia. We image high velocities in the Yangtze and Ordos cratons and low velocities underneath the East Sea (Sea of Japan), and we find that a low‐velocity zone in the midcrust is appropriate for Tibet. The model we present is intended as an alternative reference model that fits a broader range of periods to be used for further studies of regional geophysical phenomena. Key Points: We collected and processed 1 year of ambient seismic noise at over 1, 000 stations in East Asia Cluster analysis on the localized dispersion model reveals large‐scale tectonic provinces The cluster centroid models were used to create an improved 3‐D S velocity model of East Asia